Penanganan Pascapanen Kopi Pada UMKM Kopi Kutjur di Desa Sumberrejo Kecamatan Purwosari - Oktavyan Dwi Irianto; Nadhif Syathiril Anwar; Muhammad Rifal Ramadhan; Elvin Syah Huzaimi; Fatchur Rozci (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
UMKM actors are one of the jobs of the majority of the people in Sumberejo Village. The lack of information and technology for UMKM players regarding the use of E-Commerce, which really helps UMKM actors to make sales and payments online. Community empowerment activities are carried out by outreach and assistance to provide knowledge and application of E-Commerce to market UMKM products. This activity went through two stages, namely the observation and interview stages. Observation and interview activities are carried out by creating E-Commerce which consists of registration to completion. The existence of socialization regarding E-Commerce can help UMKM actors to facilitate the sale and payment of UMKM products.